Human Perception Test of Discontinuous Force and a Trial of Skill Transfer Using a Five-Fingered Haptic Interface - Takahiro Endo; Tomohiro Kanno; Mana Kobayashi; Haruhisa Kawasaki (Journal of Robotics)
In the transferring of expert skills, it takes a great deal of time and effort for beginners to obtain new skills, and it is difficult to teach the skills by using only words. For those reasons, a skill transfer system that uses virtual reality (VR) and a haptic interface technique is very attractive. In this study, we investigated the human perception of fingertip force with respect to the following changes: (1) the spatial change of the presented force, and (2) the change of the time to present the force. Based on the results of the perception experiments, we considered the skill transfer to a person's five fingers by using a five-fingered haptic interface robot.